The Effect of Problem Based Learning Model Based on Problem Solving Strategy on Critical Thinking Ability - Simbolon, Merta; Alfiani, Anisa; Jua, Selestina Kostaria (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2025)
Physics instruction that relies solely on conventional learning models is one of the factors contributing to students’ low critical thinking skills. This study aimed to examine the effect of the Problem-Based Learning (PBL) model based on a Problem-Solving Strategy on the critical thinking skills of eleventh-grade students at State Senior High School 2 Merauke in the topic of particle motion dynamics. This quantitative study employed a quasi-experimental research method using a pretest–posttest control group design. The sample consisted of class XI-4 as the experimental group and class XI-6 as the control group, selected through purposive sampling. The research procedure comprised three main stages: the preparatory stage (problem identification, literature review, development of instructional modules, and construction and validation of research instruments), the implementation stage (administration of the pretest, implementation of the intervention, and administration of the posttest), and the final stage (data analysis and formulation of conclusions). This study adopted Facione’s indicators of critical thinking skills, based on their relevance and alignment with the operational definition of critical thinking employed in this research. The results showed that the experimental class achieved a higher percentage than the control class, demonstrating that the PBL model based on a Problem-Solving Strategy had a greater impact on improving critical thinking skills compared to conventional learning models.